Flabelliferin removal by sodium salts and sodium hydroxide: pretreatment in Borassus flabellifer mesocarp - Mohd Hassan, Rodiah; Bakar, Jamilah; Abdul Rahman, Russly; Syed Muhamad, Syarifah Kharidah (Universiti Teknologi Malaysia, 2019)
The mesocarp of Borassus flabellifer has been proven to be a good potential as a food ingredient; however, the presence of bitterness in it is a deterrent to its acceptable application. Therefore, this study was aimed to determine the effectiveness of sodium hydroxide, sodium chloride, and sodium bicarbonate at 1% to 3% concentrations in reducing the bitter component, flabelliferin, in the mesocarp of B. flabellifer and how the pretreatment could affect the reduction of flabelliferin and phenolics contents. Eleven compounds were identified in the mesocarp by high-performance liquid chromatography-electrospray ionisation mass spectrometry (HPLC-ESI-MS/MS), which consisted of seven types of phenolics, two types of antocyanidins, and two types of steroidal saponins. The highest reduction at 46.2% of flabelliferin was obtained by 3% sodium hydroxide treatment. However, the removal of the bitter component was also concurrently resulted in a decrease of the total phenolic contents (0.16 mg GAE/g) of the sample. Mild treatment such as enzymatic treatment should be employed as the alternative method to preserve the antioxidant content in the mesocarp of B. flabellifer in order to promote its application in the food industry as a potential food ingredient.